Mesenchymal stem cells and their extracellular vesicles: new therapies for cartilage repair - Yang, Hongwei; Yang, Haochen; Wang, Qin; Ji, Hanzhen; Qian, Tianmei; Qiao, Yusen; Shi, Junfeng; Cong, Meng (Frontiers in Bioengineering and Biotechnology, 2025)
Cartilage is crucial for joints, and its damage can lead to pain and functional impairment, causing financial burden to patients. Due to its weak self-repair, cartilage injury control is a research focus. Cartilage injury naturally with age, but mechanical trauma, lifestyle factors and certain genetic abnormalities can increase the likelihood of symptomatic disease progression. Current treatments for cartilage injury include pharmacological and surgical interventions, but these lack the ability to stop the progression of disease and restore the regeneration of the cartilage. Biological therapies have been evaluated but show varying degrees of efficacy in cartilage regeneration long-term. The mesenchymal stem cell (MSC) therapy attracts attention as it is easily harvested and expanded. Once thought to repair via differentiation, MSCs are now known to secrete extracellular vesicles (EVs) paracrinely. These EVs, rich in bioactive molecules, enable cell communication, boost growth factor secretion, regulate the synthesis and degradation of extracellular matrix (ECM), and modulate inflammation, vital for cartilage repair. However, further research and clinical validation are still required for the application of MSC and MSC-EVs. This review highlights the current state of research on the use of MSC and MSC-EVs in the treatment of cartilage injury. It is hoped that the review in this paper will provide valuable references and inspiration for future researchers in therapeutic studies of cartilage repair.